Frequency of Intestinal Parasites in Patients Admitted to the Microbiology Laboratory of Siirt Training and Research Hospital - Leyla Gündüz; Selahattin Aydemir; Zeynep Taş Cengiz; Hasan Yılmaz (Türkiye Parazitoloji Dergisi, 2025)
Objective: The aim of this study was to determine the frequency of intestinal parasites in patients admitted to the Microbiology Laboratory of Siirt Training and Research Hospital. Methods: The study was conducted between 19.04.2021 and 30.11.2021 with a total of 300 patients (150 children and 150 adults) between the ages of 1-90 years who were referred to the Microbiology Laboratory with a request for stool sample analysis and who admitted to Siirt Training and Research Hospital with different complaints. The samples were evaluated by nativ-Lugol, formol-ethyl acetate concentration and modified acid-fast staining methods. The samples in which Entamoeba spp. eggs were detected were evaluated for Entamoeba histolytica/Entamoeba dispar antigen using Entamoeba antigen cassette test. Results: In this study, one or more than one type of intestinal parasite was found in 21.3% of 150 pediatric patients, 24% of 150 adult patients and 22.7% of 300 patients. The highest rate was Blastocystis (18%) and the lowest rate was Ascaris lumbricoides (0.7%). Although intestinal parasites were found at a higher rate in adults (24%) compared to pediatric age group (21.3%), there was no significant difference between the age groups in terms of parasite frequency in the statistical evaluation. There was a statistically significant difference between diarrhea (p=0.022) and anorexia (p=0.014) and intestinal parasite positivity. Conclusion: It was concluded that it would be appropriate to evaluate patients admitted to hospitals with complaints such as diarrhea and loss of appetite in terms of intestinal parasites. Although this study gives an idea about the prevalence of intestinal parasites in Siirt Region, there is a need for larger scale studies in the region including more people.